Intraspecific host variation plays a key role in virus community assembly - Suvi Sallinen (Nature Portfolio, 2020)
The factors that determine whether pathogens co-occur in a host are poorly understood, especially for plant viruses. Here the authors conduct field experiments with the plant Plantago lanceolata and its viruses, showing that viral co-occurrences are driven predominantly by environmental context and host genotype rather than viral interactions.